Application of Material Requirement Planning in Bracket Chamber Production: A Case Study of Automotive Component Company - Imansuri, Febriza; Ikhsanjani, Abdul Malik; Sumasto, Fredy; Dendra, Feby Gusti; Suroso, Finna; Rozi, Muhammad Fahrul (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2025)
This research was conducted to plan material needs and control the production capacity of bracket chambers at an automotive component company. The problems found were company excessively procures raw materials and unbalanced machine capacity in producing bracket chamber products. This research uses stages of the material requirements planning method, including calculating Rough Cut Capacity Planning (RCCP), Material Requirement Planning (MRP), and Capacity Requirement Planning (CRP). Implementing a MRP system enables organisations to accurately ascertain the specific kind, quantity, and timing of materials required for the production process. At the RCCP stage, capacity calculations are carried out on the CNC machine, press 1 and press 2 to find out whether the capacity of each machine can meet the company's MPS. MRP calculations are carried out to determine the optimal raw material ordering schedule using three lot sizing methods, namely Lot For Lot, Economic Order Quantity, and Period Order Quantity. At the CRP stage, each machine's capacity availability report will be made to meet bracket chamber production needs. The results of this research using RCCP and CRP analysis show that press 1 and press 2 have an unbalanced load between availability and actual demand, so it is recommended that these machines can also be used for other production so that the machines are not idle. Material requirements planning should use the Lot For Lot technique because it produces the minimum total inventory costs, namely IDR 12,710,751, with a material ordering frequency of 12 times in 1 year.